Improvements of deep vein reflux following radiofrequency ablation for saphenous vein incompetence. (February 2017) - Kim, Suh Min; Jung, In Mok; Chung, Jung Kee
Objectives: The aim of this study was to describe the changes of deep vein reflux after radiofrequency ablation for great saphenous vein incompetence. Method: The data on 139 limbs which were treated with radiofrequency ablation for great saphenous vein incompetence were prospectively collected and reviewed. Results: Deep vein reflux was present in 43 of 139 limbs (30.9%). There were no significant differences in the rate of successful closure, the incidence of procedure-related complications, and the improvements of symptoms and quality of life between the limbs with or without deep vein reflux. With a mean follow-up of 5.9 months, the peak reflux velocity and duration of reflux were improved in all limbs with deep vein reflux and it was completely corrected in 13 limbs (30.2%) after radiofrequency ablation. Conclusions: The presence of deep vein reflux does not affect the treatment outcomes of radiofrequency ablation for great saphenous vein incompetence and is improved in all patients. Deep vein reflux is not a barrier to performing radiofrequency ablation.